Slug Test in Confined Aquifers, the Over‐Damped Case: Quasi‐Steady Flow Analysis - Koussis, Antonis D.; Akylas, Evangelos (My University, 2012)
In the great majority of slug tests performed in wells fully penetrating confined geologic formations, and for over-damped conditions, the response data are evaluated with the transient-flow model of Cooper et al. (1967) when the radial hydraulic conductivity K r and the coefficient of specific storage S s are to be estimated. That particular analytical solution, however, is computationally involved and awkward to use. Thus, groundwater professionals often use a few pre-prepared type-curves to fit the data by a rough matching procedure, visually or computationally. On the other hand, the method of Hvorslev (1951), which assumes the flow to be quasi-steady, is much simpler but yields only K r estimates. In this work, we develop a complete quasi-steady flow model that includes a storage balance inside the aquifer and allows estimating K r and S s simultaneously, through matching of the well response data to a type-curve. The new model approximates the model of Cooper et al. closely and has the practical advantage that its solution type-curves are generated easily using an electronic spreadsheet, so that the optimal fit of data by a type-curve can be readily automated. © 2011, The Author(s). Ground Water
Keywords: Electronic spreadsheets; Geologic formations; Hydrogeology; Open access publishing